The Influence of Price Perceptions and Lifestyle on Purchasing Decisionss for Iphone Smartphones in Generation Z Surabaya - Ryan Ahnaf Rizky Nugroho; Ugy Soebiantoro (Universitas KH. Abdul Chalim Mojokerto, 2025)
Advances in information technology encourage people, especially Generation Z, to increasingly rely on digital devices such as smartphones. Thissstudyyaimssto evaluate the influenceeoffperceived priceeanddlifestyleeon iPhone purchase decisions among Generation Z aged 20-24 years in Surabaya. Using a non-probability approach with purposive sampling method, 100 respondents were involved. Data analysis was conducted through the Partial Least Square (PLS) method. The results showed that price perception has the mostsdominanttinfluenceeinnpurchasinggdecisions, because consumers consider the suitability between price and product quality. In addition, lifestyle also plays an important role as a supporting factor, as the iPhone is often associated with a modern image and a symbol of social status. The findings provide strategic insights for businesses in designing more effective marketing approaches that suit the characteristics of young consumers.